CORRUPTION CRIMINAL SANCTIONS WITH VALUES OF JUSTICE-BASED - Zulfiani Zulfiani (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Corruption is one of society's disorientation and is in the same state as other types of crimes such as theft, which has existed since the human are living as society. The problem is that the corruption is increasing in line with prosperity and technological advancement. In fact, when a nation is advancing in its development, it encourages people to have more need so that they will engage in corruption. Based on these descriptions, in the preparation of this paper the authors will describe, how corruption criminal sanctions with values of justice? In this study, the author applies qualitative research methods, constructive approach, and also applies primary data and secondary data. The techniques of observation and in-depth interviews with key informants are applied for collecting primary data. Last, data analysis technique is applied to the primary data. Corruption prevention policies do not give deterrent effect to the corruptor. The investigation and prosecution policy in cases of corruption, supposedly having orientation for reimbursing the state and also aiming deterrent effect by providing severe criminal sanctions. No arrest for suspect of corruption (although the state has been paying losses) is reducing the deterrent effect or even not all. For the sake of justice, the judge should see Article 5 of Law No. 48 of 2009, it is clear that the reconstruction of criminal responsibility and accountability of the administration are related to the values of justice, the values of divinity and legal values that live in the community (the living law) so we need to develop justice characterized by Indonesia, which is “justice of Pancasila”, which implies “justice of deity,” “fairness humane (humanistic)”, “justice that is democratic, nationalistic, and social justice”. This means, justice upheld is not just formal justice, but substantial justice. Keywords: corruption, criminal sanctions, the value of justice